ChemInform Abstract: Caesium Iodide as an Efficient Catalyst for Synthesis of N‐Substituted Azepines via Tandem Michael Addition and Cyclization under Aqueous Conditions. Issue 24 (2nd June 2014) - Eshghi, Hossein; Momen, Sara; Gholizadeh, Mostafa; Vakili, Mohammad
Abstract Reuse of the catalyst does not lead to a significant decrease in its activity.